Post partum haemorrhage, estimated blood loss at delivery and relationship with duration, concentration and total dose of exogenous oxytocin administered in labour. (16th November 2010) - Hannon, T; Rosales, C; Walker, L; Moody, J; Robson, SC
Abstract : Background: Post partum haemorrhage (PPH) is a major cause of maternal morbidity. Induction and augmentation of labour with exogenous oxytocin are associated with increased estimated blood loss (EBL) at delivery, and major PPH (EBL >1000 ml). Little data are available on the impact of duration, highest dose and total dose of oxytocin on EBL and major PPH. Setting: Tertiary obstetric unit with 6500 births p.a. Methods: Retrospective review of consecutive sets of obstetric notes returned for postnatal filing (excluding elective Caesarean section). Oxytocin dose was calculated from dose regime documented on partogram. Blood loss was estimated by the delivering clinician. Results: 440 notes were reviewed, 201 had exogenous oxytocin. Overall major PPH rate was 7.05% (consistent with annual unit data). Compared to no use of oxytocin, relative risk of major PPH rises to 2 (95% CI 1.5 to 2.77) with more than 4 h of oxytocin, and 5.4 (95% CI 2.57 to 11.24) after 12 h. There is a linear relationship between increase in mean estimated blood loss and increasing duration, maximum dose and total dose of oxytocin (analysis of variance p<0.0001 for each). There is also a significant increase in rates of major PPH with increasing duration, maximum dose and total dose of oxytocin (χ 2 test for trend <0.0001 for each). Discussion: Mean blood loss and rates of major PPH increase with increasing use of exogenous oxytocin. Major PPH rates in women on exogenous oxytocin for longer than 4 h in our unit approaches 13%. Further research is needed into reducing the risk of haemorrhage in this group.